Neutron irradiation influence on the silicon voltage limiter parameters - Rakhmatov, A.Z.; Tashmetov, M.Yu.; Sandler, L.S. (Вопросы атомной науки и техники, 2012)
The influence of neutron irradiation on breakdown voltage (Ubd) and limitation voltage (Ulim) is investigated in silicon voltage limiter. The coefficient Kρ is basic radiation parameter, forming dependences Ubd = f (F) and Ulim = f (F), which determines the dependence of basic charge carriers concentration in silicon from neutron fluencies. The mechanisms, which form the Ulim value after neutron irradiation are determined. On basis of obtained results analysis is proposed the model, which makes it possible to forecast changes in the breakdown voltage and limitation voltage, which occur as a result the neutron irradiation of voltage limiter.